Effectiveness of the extended mean-variance model using fuzzy approach for portfolio selection in Malaysian stock market / Zulkifli Mohamed ...[et al.] - Mohamed, Zulkifli; Ahyak, Ruzidah; Zainal Abidin, Sazali; Mohd Daud, Norzaidi (Institute of Business Excellent and University Publication Center (UPENA), 2010)
Purpose of the study is to investigate the effectiveness of the extended mean-variance model using fuzzy approach in maximizing portfolio diversification benefit in the Malaysian stock market. 10 types of portfolios involving 300 listed companies in Bursa Malaysia from 1998 to 2009 were used as a sample for the extended model testing. Linear programming optimization tool was used to derive efficient portfolios. Portfolio superiority then been measured by using the efficient frontier index (EFI). Empirical evidence revealed that the extended meanvariance model is able to maximize portfolio’s diversification benefit in the Malaysian stock market compared to the conventional mean-variance and the VBS fuzzy models. The result provides on how the Malaysian investors could improve on their investment strategy. This study is perhaps one of the first to address portfolio diversification benefit using the extended mean-variance model in the Malaysian stock market.